Synthesis and in vitro antimicrobial activity of new steroidal hydrazone derivatives - Shailesh Mistry; Akhilesh Kumar Singh (Future Journal of Pharmaceutical Sciences, 2022)
Abstract Background For many years, various drugs have been used for the treatment of infectious diseases but some bacterial microorganisms have induced resistance to several drugs. In a search of new antimicrobial agents, a series of new steroidal hydrazones were designed and synthesized. Result The structures of the compounds were established based on the spectral data. The in vitro antimicrobial activity of some newly synthesized compounds against bacteria and fungi was studied. Conclusion New compounds showed better or similar antimicrobial activity. Designing more efficient steroidal hydrazones from ketosteroid based on the current study may successfully lead to the development of antimicrobial agent. Graphical abstract